2021
DOI: 10.1002/ange.202110819
|View full text |Cite
|
Sign up to set email alerts
|

High‐Affinity Dimeric Aptamers Enable the Rapid Electrochemical Detection of Wild‐Type and B.1.1.7 SARS‐CoV‐2 in Unprocessed Saliva

Abstract: We report as imple and rapid saliva-based SARS-CoV-2 antigen test that utilizes an ewly developed dimeric DNAa ptamer,d enoted as DSA1N5, that specifically recognizes the spike proteins of the wildtype virus and its Alpha and Delta variants with dissociation constants of 120, 290 and 480 pM, respectively,a nd binds pseudotyped lentiviruses expressing the wildtype and alpha trimeric spike proteins with affinity constants of 2.1 pM and 2.3 pM, respectively.T o develop ah ighly sensitive test, DSA1N5 was immobili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 77 publications
0
48
0
Order By: Relevance
“…Previous reports have found that Electrochemical Impedance Spectroscopy (EIS)-based biosensors rapidly detect bioreceptors associated with SARS-CoV-2 infection, with high sensitivity, specificity and reliability [ [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] ]. In such biosensors, bioreceptors are anchored on the working electrode surface to directly bind to target molecules specifically, generating changes in the interfacial properties in a concentration-dependent manner [ [18] , [19] , [20] ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have found that Electrochemical Impedance Spectroscopy (EIS)-based biosensors rapidly detect bioreceptors associated with SARS-CoV-2 infection, with high sensitivity, specificity and reliability [ [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] ]. In such biosensors, bioreceptors are anchored on the working electrode surface to directly bind to target molecules specifically, generating changes in the interfacial properties in a concentration-dependent manner [ [18] , [19] , [20] ].…”
Section: Introductionmentioning
confidence: 99%
“…These drawbacks thereby result in potential tradeoffs in terms of sensitivity, specificity and user-friendliness. On the other hand, aptamers, known as “chemical antibodies”, have been recommended as a powerful class of bioreceptors with several features of high specificity and affinity, reliable and cost-effective synthesis, ease of modification, and excellent feasibility to combine with many DNA-based reactions for signal amplification [36] , [37] , [38] . These advantages enable aptamers to be promising bioreceptors, with a wide range of applications for biosensors [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] .…”
Section: Introductionmentioning
confidence: 99%
“…The selectivity and affinity of monovalent aptamers are easily subjected to sample conditions, including temperature, PH, ionic strength, interference, viscosity, etc [ 198 ]. Several strategies could be taken to address this issue: 1) Using multivalent spatial recognition patterns [ 114 , 124 ]. Generally, multivalent aptamers exhibit more excellent recognition and binding abilities than monovalent aptamers.…”
Section: Discussion and Perspectivementioning
confidence: 99%
“…As one of the most sensitive transduction approaches, electrochemical impedance spectroscopy (EIS) has been widely applied for sensing. Zhang et al [ 114 ] first reported a bivalent aptamer (DSA1N5) nanoprobe-based EIS aptasensor, Cov-eChip, to detect original SARS-CoV-2, Delta, and Alpha variants of this virus in unprocessed saliva. In this sensor, the DSA1N5 bivalent aptamer was engineered by ligating two monomers (MSA1 and MSA5), and it was immobilized on gold electrodes to generate an electrochemical impedance signal ( Fig.…”
Section: Viral Proteins and Their Detectionmentioning
confidence: 99%